Evaluation of ethanol extract of Morus nigra L. as an inhibitory agent for DNA-Advanced glycation end product (DNA-AGEs) (Indian Journal of Biochemistry and Biophysics (IJBB), 2024)
In the developing countries there is a direct correlation between the amount of consumed foods containing starch and the increase in metabolic diseases. In contrast to glucose, fructose cannot be detected in the blood by insulin. Thus, it participates in lipogenesis and increases intracellular lipid accumulation.Reducing sugars results in the development of AGEs (Advanced Glycation End-Compounds) in biological macromolecules as well as some reactive products. These products can cause tissue damage by accumulating in the pathogenesis of a number of diseases by various mechanisms.AGEs can damage antioxidant systems by increasing ROS (reactive oxygen species). In this study, pBR322 DNA was incubated with different concentrations of fructose for 5 days. Damage to the structural system of fructosylated DNA was detected by an increase in fluorescence intensity and hyperchromicity. For five days, fructosylated DNA was treated with varying quantities of Morus nigra L. soxhlet extract and quercetin, and its impact on DNA structural damage was noted. The reduction in hyperchromicity and fluorescence intensity revealed the protective impact of quercetin and M. nigra L. extract on DNA. It has been found that the extract of M. nigra L. and quercetin both scavenge free radicals and reduce fructose-induced DNA damage.